Biomimetics: Biomimetic Microfingerprints for Anti‐Counterfeiting Strategies (Adv. Mater. 12/2015). (March 2015) - Bae, Hyung Jong; Bae, Sangwook; Park, Cheolheon; Han, Sangkwon; Kim, Junhoi; Kim, Lily Nari; Kim, Kibeom; Song, Suk‐Heung; Park, Wook; Kwon, Sunghoon
Abstract : W. Park, S. Kwon, and co‐workers discuss biomimetic microfingerprints for anti‐counterfeiting strategies on page 2083. In the described strategy, polymeric particles are encrypted with randomly generated silica film wrinkles, which act as codes that are as unique as human fingerprints. These codes are tunable on various geometries.